The management of sloping lands for sustainable agriculture in Malaysia - Zainol I; Mahmud A W (In : Report of the annual review meeting on Asialand management of sloping lands in Asia, Guiyang, China, 2-8 September 1993, 1994)
At least 40 000 ha of land are cleared annually for rubber planting in Malaysia. Since most of these areas consist of sloping lands, the need for conservation-oriented farming systems is imperative. Experience shows that intercropping results in better growth of rubber and can reduce the immaturity period. This paper discusses the sustainability of intercropping annual crops under rubber, the changes in soil fertility as affected by different soil and crop management systems, and the practicability of high-input technology.
Source Year: 1996
Keywords: Intercropping; Malaysia; Sustainable agriculture